(untitled) (Педагогіка вищої та середньої школи, 2022)
The article deals with a number of problems associated with the implementation of ICT (Information and Communication Technology) in higher chemical education. In particular, the advisability of using this method (MM2-simulation) in the investigation of chemical structures of biomolecules of proteinaceous protein nature has been shown.